Vaccination of Newborns in Obstetric Institutions as an Indicator of the Quality of Medical Care for Babies - I. V. Feldblium; M. Yu. Devyatkov; M. Kh. Alyeva (Эпидемиология и вакцинопрофилактика)
Relevance Hepatitis B and tuberculosis are a serious global health problem. Babies under one are at high risk of a severe form of these diseases and mortality. Immunization of newborns plays a key role both in the individual prevention of hepatitis B and tuberculosis and in reducing the burden of these infections in general.The purpose of the study was to assess the timeliness of vaccination newborns against hepatitis B and tuberculosis and to determine the causes of deviations from national vaccine schedule. Materials and methods. The coverage of vaccination against hepatitis B and tuberculosis was studied according to the case history of newborns (form No. 097/у, N = 672) and form No. 6 «Information on the contingents of children, adolescents and adults vaccinated against infectious diseases», the state of child morbidity - according to form No. 2 «Information on infectious and parasitic diseases» for 2006–2018. Anonymous questioning of pregnant women was conducted to assess adherence to vaccination (N = 73).Results. The average proportion of newborns who were vaccinated against hepatitis B in the maternity hospital over a 12-year follow-up period was 82.2%, against tuberculosis was 85.1%. More than 50.0% of children weren’t vaccinated against hepatitis B and about 20% of children weren’t not vaccinated against tuberculosis due to the vaccine hesitancy of their parents. 72.6% respondents agree that vaccination is important, 73.9% one that vaccination is effectiveness and only 50.6% one that vaccination is safety. The adherence to vaccination of newborns against tuberculosis is higher than against hepatitis B (78.1 and 69.9% respectively). There is a tendency to increase the number of children from 0 to 14 years old who are not vaccinated against both tuberculosis and hepatitis B.Conclusion. The lack of immunization of newborns in neonatology departments is a risk factor for low future immunization rates for children, infection of children with hepatitis B virus and mycobacterium tuberculosis, as well as parental distrust in vaccination in general.